Type of in vitro cultivation influences cytoadhesion, knob structure, protein localization and transcriptome profile of Plasmodium falciparum - Tilly, Ann-Kathrin (Sci Rep, 2015)
In vitro cultivation of Plasmodium falciparum is critical for studying the biology of this parasite. However, it is likely that different in vitro cultivation conditions influence various aspects of the parasite’s life cycle. In the present study two P. falciparum isolates were cultivated using the two most common methods, in which AlbuMAX or human serum as additives are used, and the results were compared. The type of cultivation influenced the knob structure of P. falciparum-infected erythrocytes (IEs). IEs cultivated with AlbuMAX had fewer knobs than those cultivated with human serum. Furthermore, knob size varied between isolates and is also depended on the culture medium. In addition, there was a greater reduction in the cytoadhesion of IEs to various endothelial receptors in the presence of AlbuMAX than in the presence of human serum. Surprisingly, cytoadhesion did not correlate with the presence or absence of knobs. Greater numbers of the variant surface antigen families RIFIN, STEVOR, and PfMC-2TM were found at the IE membrane when cultivated in the presence of AlbuMAX. Moreover, the type of cultivation had a marked influence on the transcriptome profile. Compared with cultivation with human serum, cultivation with AlbuMAX increased the expression of approximately 500–870 genes.